Alimentos que debo consumir para crecer fuerte y sano - Blas Cueva, Deysi Yobana (2019)
Habits for healthy food consumption have been replaced by eating food that harm people's physical, mental and biological development. Fast food is being assumed and consumed more and more, which deteriorates health in children, being a tendency to obesity, problem in school performance, diabetes and even certain types of cancers, just to name a few; These processed products high in sugars, carbohydrates and minerals degenerate blood vessels and cells. Global policies have been adopting a series of measures to regulate the consumption of so-called junk food, forcing producing companies to inform consumers about the content of each product with a high index of sugar, carbohydrates or minerals, so that it is the buyer who determines the purchase or not of the product. However, this is not enough, because children who go to the supermarket or the grocery store without company, consume without taking into account the indications. The looks nowadays are oriented to the consumption of a balanced diet with well-informed diets that prevent diseases and the accelerated deterioration of health. In our region ancestral customs have taught us that the consumption of nutritious products of healthy cultivation and consumption improve the quality of life in the future, these practices are demonstrated in the physical and biological state of those who have had a healthy life with products of origin animal like: guinea pig, fish, red meat, milk. Or plant-based foods: Olluco, ocas, quinoa, quiwicha, beans and food offered by the qaliwarma program